The Devil's Haircut: Investor–State Disputes over Debt Restructuring. (September 2019) - DiGiuseppe, Matthew; Shea, Patrick E.
When do private creditors versus debtor states accept a greater burden in resolving sovereign debt crises? In this study, we argue that distributive politics helps explain the "haircut"—or losses—private creditors take in debt restructuring cases. Despite the expected convergence of partisan policies in a globalized economy, we argue that right and left leaders extract different settlements in debt negotiations. Left governments, representing constituents most likely to be hurt from higher debt repayment, credibly demonstrate more bargaining power and extract greater concessions from creditors. Distributive politics, however, is an indeterminate factor in explaining states entrance into debt negotiations. We use recently released data on the outcome of sovereign debt restructuring cases between states and private creditors from 1975 to 2013 to test our expectations. Results from a double-hurdle model indicate that creditors receive a larger haircut when negotiating with left governments.